Experimental study on composite mechanical properties of a double-deck prestressed concrete box girder. Issue 12 (September 2019) - Zhu, Mingqiao; Yan, Zefeng; Chen, Lin; Lu, Zhongliang; Chen, Y Frank
A series of tests were carried out on a scaled (1:8) double-deck prestressed concrete box girder in this study, aiming to study the structural response and failure mechanism of the box girder under prestressed axial compression, transverse bending, and torsion. The test results, such as the twist angle, crack development, and distortion of the box girder, were analyzed in detail. The results show that (1) the box girder eventually suffered lateral bending damage, and the cross-section of the support distorted severely; (2) torsional cracking occurred in the pure torsion region at the mid-span, but the longitudinal and transverse rebars did not yield, indicating that the pure torsion section of the box girder was still in the early stage of torsion failure; and (3) after the cracking of the box girder, stress redistribution phenomenon occurred, resulting in obvious nonlinear strain variations. Comparison of the longitudinal and transverse steel strains showed that transverse steel withstood the most shear stress during the early stage of torsion.